Understanding the labour market for older workers: a survey - John S. Heywood; William Stanley Siebert (Institute for the Study of Labor (IZA), 2009)
The paper asks why retirement can be so abrupt in countries such as France (1/2% of the workforce over 65), yet staged in Japan (8% over 65). We find part of the answer in tax laws that prevent people working and receiving a pension, and make little allowance for fair pension increases if retirement is deferred. While these laws have begun to change, we find another part of the answer in employment protection laws. These laws coupled with inflexible collectively agreed wages make employers choosy about hiring the old. The advent of age discrimination law reinforces employment protection and may well reduce older workers' hiring opportunities especially where wages are rigid.
urn:nbn:de:101:1-20090306267
Keywords: I38; J32; J71; 330; Mandatory retirement; deferred pay; age discrimination; older workers; Altersgrenze; Flexible Altersgrenze; Ältere Arbeitskräfte; Arbeitsmarktdiskriminierung; Einkommensteuer; Kündigungsschutz; Ökonomischer Anreiz; OECD-Staaten